ANALYSIS OF MARRIAGE REGISTRATION IN GAMPONG ASAM PEUTEK WITHOUT PRECEDING RAFA' FROM A JURIDICAL PERSPECTIVE - Nur Asiyah; Fatimah (Jurnal Hukum Samudra Keadilan, 2024)
Marriage registration is the administrative data collection on marriages handled by marriage registrar officers with the aim of creating legal order. This research shows that regulations regarding examining marriage documents are regulated in Minister of Religion Regulation Number 19 of 2018 concerning Marriage Registration. Because checking documents is one of the processes of registering a marriage. However, the examination of this document is administrative in nature, so it does not determine whether a marriage is valid or not. The type of research carried out by the author is field research using qualitative methods, while the data collection techniques used are observation, interviews, and documentation. The analysis used is an inductive method, namely by presenting specific empirical facts from the research results and then ending with general conclusions. From this research it can be concluded that marriage registration was not carried out in accordance with existing laws and regulations. However, this is not a benchmark for whether a marriage is valid or not because document checks are administrative in nature. It's just that in the case of marriage registration, the documents were not checked, which is one of the stages of marriage registration. Examination of marriage documents, commonly called rafak, aims to ensure the suitability of the data of the prospective bride and groom and also that there are no obstacles to carrying out the marriage.